Asymmetric Y-branch plastic optical fiber coupler - Ehsan, Abang Annuar; Shaari, Sahbudin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
An acrylic-based asymmetric Y-branch plastic optical fiber (POF) coupler has been developed. The optical device is based on a Y-branch coupler design with a middle high index contrast waveguide taper and open space region for output fiber displacement. The middle waveguide taper is constructed on the acrylic block itself without using any additional optical waveguiding medium injected into the engraved taper region. The waveguide taper allows light rays to propagate by total internal reflection and this is achieved by having the material surrounding the waveguide taper to be of a lower refractive index (RI) than that of acrylic (RI of acrylic is 1.49). The area surrounding the waveguide taper has been designed in such a way that it is surrounded by an open air with an RI of 1.0. The high index contrast structure enables large splitting angle and shorter device length. Input and output POFs are inserted into this device structure in such a way that they are passively aligned to the middle waveguide taper structure. A simple attenuation technique based on lateral displacement of two fibers has been proposed and presented for the non-symmetrical coupling ratios. Numerical analysis has been made on the lateral displacement of the output fibers which shows that the device is able to generate non-symmetrical coupling ratios. A simple relationship between the coupling ratios and output fiber separation has been obtained. Device modeling has been performed using non-sequential ray tracing technique on the Y-branch coupler performing as a simple 3 dB coupler with excess loss of 1.83 dB and a coupling ratio of 50:50. The non-symmetrical coupling ratios of the device have been simulated by varying the lateral displacement of one output fiber from 0.1 mm to 4.4 mm. The results for the coupling ratios against the fiber displacement have been obtained and show how the device can be operated as an asymmetric Y-branch POF coupler.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 807-816
Keywords: optyka; acrylic; asymmetric; coupler; plastic optical fiber (POF); waveguide taper; Y-branch